2013
DOI: 10.1007/s00125-013-3017-7
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of autoantibodies in patients with long duration type 1 diabetes

Abstract: No abstract [Research letter

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 10 publications
1
13
0
1
Order By: Relevance
“…Even after >14 years of diabetes duration, 34% of the patients were positive for GADA, and carriers of the LPP risk variant had a 36% increased probability for GADA positivity. This frequency of GADA positivity is comparable to other cohorts of patients with long-standing diabetes ( 31 , 32 ). Although type 1 diabetes is thought to result from an irreversible destruction of β-cells, some long-standing patients have detectable functioning β-cells ( 33 35 ), indicating either surviving β-cells or continued renewal due to ongoing autoimmune destruction.…”
Section: Discussionsupporting
confidence: 85%
“…Even after >14 years of diabetes duration, 34% of the patients were positive for GADA, and carriers of the LPP risk variant had a 36% increased probability for GADA positivity. This frequency of GADA positivity is comparable to other cohorts of patients with long-standing diabetes ( 31 , 32 ). Although type 1 diabetes is thought to result from an irreversible destruction of β-cells, some long-standing patients have detectable functioning β-cells ( 33 35 ), indicating either surviving β-cells or continued renewal due to ongoing autoimmune destruction.…”
Section: Discussionsupporting
confidence: 85%
“…However, another study in individuals with younger onset showed that high positivity for ZnT8A at diagnosis was associated with lower C-peptide levels and increased insulin dose within the first 2 years after diagnosis, despite similar levels at disease onset [56]. In a minority of individuals where ZnT8A persist for decades after diagnosis, cross-sectional studies have also failed to reach a consensus about the relationship between ZnT8A and C-peptide [5759]. These contrasting findings could be explained if age at diagnosis influences this association.…”
Section: Znt8a As a Biomarker Of Insulin Secretory Capacity Post Diagmentioning
confidence: 99%
“…[ 47 ] Nevertheless, ZnT8A could be detected within 25 years after T1DM onset (6.7%), and even in patients with T1DM for more than 50 years. [ 47 49 ]…”
Section: Linical a Pplications Of mentioning
confidence: 99%